2022
DOI: 10.1111/eip.13337
|View full text |Cite
|
Sign up to set email alerts
|

An integrated substance use treatment model for young adults with first‐episode psychosis: A naturalistic pilot evaluation

Abstract: Aim Approximately 50% of individuals with first‐episode psychosis meet criteria for a substance use disorder and these concurrent disorders are associated with worse long‐term outcomes. Psychosocial interventions, including motivational interviewing as well as cognitive and behavioural therapies, have shown some evidence for effective treatment in substance use disorders; however, there is a paucity of existing studies that have successfully examined these interventions in first‐episode psychosis. Methods Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In this review, MI interventions showed significant reductions in substance use and other associated health benefits in seven of the 11 included studies [32, 34, 36-38, 41, 42]. These findings were consistent with results found in HICs [9,[18][19][20][21][22]. There are various potential reasons why the remaining four studies [33,35,39,40] yielded less favourable outcomes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this review, MI interventions showed significant reductions in substance use and other associated health benefits in seven of the 11 included studies [32, 34, 36-38, 41, 42]. These findings were consistent with results found in HICs [9,[18][19][20][21][22]. There are various potential reasons why the remaining four studies [33,35,39,40] yielded less favourable outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…The impact of MI as a strategy for addressing substance use in HICs is generally favourable, although it has yielded varied outcomes [9,[18][19][20][21][22][23][24]. However, there is far less evidence to support its effectiveness in LMICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substance use disorder is a further important co-morbidity that, when treated, can prevent or reduce the severity of DD, as has been demonstrated in patients with first-episode psychosis. 53 de Portugal et al, using DSM-IV-TR criteria, carried out a cross-sectional…”
Section: Primary and Secondary Preventive Strategies On An Individual...mentioning
confidence: 99%
“…Continuing SUD for young adults enrolled in CSC was associated with stopping services, poorer life skills, worse symptoms, and lower rates of medication adherence (Oluwoye et al, 2019; Patel et al, 2016; Schoeler et al, 2017), as well as decreased ‘graduation’ rates (Fraser et al, 2023). Outside of CSC, one intervention for young adults with EP that used motivational interviewing techniques and relapse prevention skills training that prioritized skill acquisition was found to significantly increase young persons' motivations to decrease use frequency (Herman et al, 2022). Additionally, Bello and Dixon (2022) highlight the use of integrated mental health and substance use interventions as best practice for EP.…”
Section: Introductionmentioning
confidence: 99%